Analisis Struktur Biaya dan Efisiensi Ekonomi Usaha Tani Tembakau: Studi Kasus Kelompok Tani Batu Daun di Desa Batuan, Kabupaten Sumenep - Hopid Hopid; Sindi Arista Rahman; Darma Jasuli; Ribut Santosa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Tobacco is a leading commodity that forms the foundation of the rural economy, but its cultivation faces challenges in the form of labour intensity, significant capital requirements, and farmers' lack of understanding of systematic cost structures. This study aims to analyse the production cost structure and evaluate the economic efficiency of tobacco farming managed by the Batu Daun Farmer Group in Batuan Village, Sumenep Regency. The research method used a qualitative descriptive approach with data collection through in-depth interviews with the head of the farmer group, field observations, and analysis of financial documents as secondary data. The analysis focused on identifying fixed and variable costs, as well as evaluating economic performance using the Break Even Point (BEP) and Revenue-Cost Ratio (R/C) indicators. The results showed that the total production cost was IDR 28,597,500 (fixed costs of IDR 3,450,000 and variable costs of IDR 25,147,500) for the production of 2,800 kg of tobacco with a gross income of IDR 70,000,000. The R/C ratio value of 2.44 (>1) indicates that the business is operating efficiently and profitably, while the BEP of 215.4 kg shows that actual production far exceeds the break-even point, meaning that the business is in an economically safe zone. The results of the study conclude that the tobacco farming business of the Batu Daun Farmer Group is economically viable and efficient.